Peer tutoring during language code-switching lectures as a teaching strategy in multilingual classes - du Plessis, Sandra (South African Journal of Higher Education, 2018)
Peer tutoring during language code-switching lectures as a teaching strategy in multilingual classes ABSTRACT Educators in higher education in South Africa often find that some African/Black first-year students may not fully comprehend concepts explained in English or have the fluency to express themselves clearly in academic tasks. The project investigated the benefits of code-switching to the students’ first languages by peer tutors. A descriptive design within a quantitative framework was selected and a questionnaire was designed as survey instrument. After each set of lectures students were divided into first language groups and a peer tutor summarised the lectures in the group’s first languages, followed by group discussions. After the module the students completed the questionnaire. The findings indicate that the students were in general positive about peer tutoring and that code-switching provided clarity, allowed participation, provided peer support, and imparted a feeling of being valued. It is concluded that the students’ first languages can be regarded as a resource to draw on in an English environment. KEYWORDS: Code-switching, multilingual classes, peer tutoring, student support, teaching strategy in higher education.